Application of complete feed formulated from agriculture by products with undegraded protein supplementation on beef cattle productivity. - Suhartanto, Bambang; Widyobroto, Budi Prasetyo; Budisatria, I Gede Suparta; Kustantinah, Kustantinah; Utomo, Ristianto (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
Complete feed formulated from agriculture by-products (corn cob, rice bran, cassava pomace, molasses, kapok seed, copra and soybean meal) containing, 12% of crude protein and 64% of TDN was pelleted before being applied to beef cattle raised in livestock farmer's group. Ten males Ongole crossbred cattle of 1.5 to 2.5 years old weighing 259.7=27.0kg were randomly divided into two groups. First group as the control received act libitum local feed (mixed from rice straw, elephant grass, peanut haulm, cane top and native grass), supplemented with 4kg of rice bran/headiday. Second group received complete feed (2.6% of body weight) and 5g undegraded protein /kg°.''. Undegraded protein was prepared from soybean meal protected using 1% formaldehyde (w/v). After 4 weeks of adaptation, gain weight and feed consumption were collected for 13 weeks. The cattle were slaughtered to evaluate carcass percentage and meat bone ratio. Income over feed cost was calculated by the difference between daily feed cost and gain weight price. The result showed that crude protein. dry and organic matter consumption of control group: 1.35kg, 10.96kg, and 8.25kg/head respectively were higher (P<0.05) than those the group received complete feed (respectively 1.09kg, 7.9kg and 7.4kg/head). The average daily gain and carcass percentage of control group (0.573kg and 44.15%) was lower (P<0.05) than that the complete feed group (0.868kg and 49.98%). Feed conversion ratio (FCR) in complete feed groups (9.17) was significantly better (P<0.05) than the control group (20.41). However, there was no significance different between the both group on meat bone ratio (4.62 and 5.34 for the control and the complete feed group). Income over feed cost was 80,131.0 and 230,297.3 IDR/day/head for the control and treatment of complete feed group respectively. It can be concluded that application of complete feed formulated from agriculture by-product supplemented with undegraded protein improved beef cattle productivity.